The Fiefdom Problem - Michael Scriven (The Evaluation Center at Western Michigan University, 2004)
This editorial discusses the challenges created when groups and organizations develop their own, often conflicting, definitions and conceptual frameworks in the field of evaluation. Avenues for resolving these issues are presented.